KLF11 Protects against Venous Thrombosis via Suppressing Tissue Factor Expression - Liang, Wenying; Lu, Haocheng; Sun, Jinjian; Zhao, Guizhen; Wang, Huilun; Guo, Yanhong; Eitzman, Daniel; Chen, Y Eugene; Fan, Yanbo; Zhang, Jifeng (Thrombosis and Haemostasis, 2021)
Krüppel-like factors (KLFs) play essential roles in multiple biological functions, including maintaining vascular homeostasis. KLF11, a causative gene for maturity-onset diabetes of the young type 7, inhibits endothelial activation and protects against stroke. However, the role of KLF11 in venous thrombosis remains to be explored. Utilizing stasis-induced murine deep vein thrombosis (DVT) model and cultured endothelial cells (ECs), we identified an increase of KLF11 expression under prothrombotic conditions both in vivo and in vitro. The expression change of thrombosis-related genes was determined by utilizing gain- and loss-of-function approaches to alter KLF11 expression in ECs. Among these genes, KLF11 significantly downregulated tumor necrosis factor-α (TNF-α)-induced tissue factor (TF) gene transcription. Using reporter gene assay, chromatin immunoprecipitation assay, and co-immunoprecipitation, we revealed that KLF11 could reduce TNF-α-induced binding of early growth response 1 (EGR1) to TF gene promoter in ECs. In addition, we demonstrated that conventional Klf11 knockout mice were more susceptible to developing stasis-induced DVT. These results suggest that under prothrombotic conditions, KLF11 downregulates TF gene transcription via inhibition of EGR1 in ECs. In conclusion, KLF11 protects against venous thrombosis, constituting a potential molecular target for treating thrombosis.
Keywords: endothelial cells; early growth response protein 1; Krüppel-like factor; tissue factor; venous thrombosis